Obstructive Sleep Apnea Risk, Body Fat, and BMI in Pulmonary Tuberculosis Patients - Nurul Isnaeni Jumaide; Edward Pandu Wiriansya; Marzelina Karim; Asrini Safitri; Ahmad Ardhani Pratama (Ann Publisher, 2026)
Background: Obstructive sleep apnea (OSA) is a common sleep-related breathing disorder significantly associated with body composition abnormalities. Pulmonary tuberculosis (TB) causes structural lung damage that may predispose patients to sleep disturbances, yet the relationship between OSA and body composition in TB populations remains inadequately explored. Aim: This study aimed to investigate the association between OSA severity and body composition measures including total body fat, visceral fat, subcutaneous fat, and body mass index (BMI) among pulmonary TB patients. Methods: A cross-sectional analytical observational study was conducted at RS Ibnu Sina YW-UMI Makassar from August to November 2025. Eighty-five pulmonary TB patients were selected through purposive sampling. OSA risk was assessed using the STOP-BANG questionnaire, while body composition was measured using bioelectrical impedance analysis. Chi-square tests were performed to examine associations between variables with significance set at p<0.05. Results: Significant associations were found between OSA severity and all body composition parameters: total body fat (p=0.004), visceral fat (p=0.000), subcutaneous fat (p=0.005), and BMI (p=0.000). Severe OSA showed highest prevalence of very high total body fat (46.4%), elevated visceral fat (60.7%), high subcutaneous fat (57.1%), and obesity grade 1 (35.7%). Moderate OSA occurred predominantly in underweight patients (50.0%), revealing a U-shaped BMI-OSA relationship. Conclusions: Visceral fat demonstrated the strongest association with OSA severity in pulmonary TB patients. Comprehensive body composition assessment provides superior clinical utility compared to BMI alone for OSA risk stratification. Implementation. These findings support integrating body composition monitoring into TB management protocols and provide foundation for personalized interventions addressing both infectious disease treatment and metabolic health optimization